2016
DOI: 10.1002/jor.23300
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the COL2A1 mutation in idiopathic osteonecrosis of the femoral head

Abstract: Idiopathic osteonecrosis of the femoral head (idiopathic ONFH) is an ischemic disorder resulting in necrosis of the subchondral bone of the femoral head. COL2A1 mutations, including c.3508G>A, have been reported to be involved in its etiology. However, the etiological role of COL2A1 mutations in idiopathic ONFH remains controversial, because the pathology of idiopathic ONFH is ischemic necrosis, not epiphyseal dysplasia usually seen in the diseases caused by COL2A1 mutations. The purpose of this study is to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…A meta-analysis to assess the association of the 4b/a, G894T, and T786C polymorphisms of endothelial nitric oxide synthase with ONFH risk showed a significant correlation between allele a of the 4b/a polymorphism and idiopathic ONFH 20 . As chondrogenesis-specific transcription factor, collagen type II alpha-1 gene (COL2A1) mutations, including c.3508G > A, have been reported to be involved in idiopathic ONFH etiology 21 . OPG, as protein encoded by tumor necrosis factor superfamily11B (TNFRSF11B), is an osteoblast-secreted decoy receptor that functions as a negative regulator of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis to assess the association of the 4b/a, G894T, and T786C polymorphisms of endothelial nitric oxide synthase with ONFH risk showed a significant correlation between allele a of the 4b/a polymorphism and idiopathic ONFH 20 . As chondrogenesis-specific transcription factor, collagen type II alpha-1 gene (COL2A1) mutations, including c.3508G > A, have been reported to be involved in idiopathic ONFH etiology 21 . OPG, as protein encoded by tumor necrosis factor superfamily11B (TNFRSF11B), is an osteoblast-secreted decoy receptor that functions as a negative regulator of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic association studies suggest that mutations involved in cartilage constitution, bone metabolism, detoxification, coagulation system or vascular endothelium function might participate in the aetiology of osteonecrosis. [19][20][21][22] Based on an initial screening of exome sequencing and the subsequent confirmation of Sanger sequencing of this study, pathogenic mutations were identified in COL2A1 in a Chinese family with LCPD. The COL2A1 gene is localized at 12q13.11-q13.2 and about 30 kb in length with 54 exons, which provides a key element for the production of type II collagen.…”
Section: Discussionmentioning
confidence: 97%
“…[38][39][40] To date, the knowledge on the development of LCPD in humans is limited because of the vast number of mutations found in the COL2A1 gene and the variability in the clinical phenotype. [41,42] It is apparent that the process in which mutations in collagens alter connective tissues is complicated and cannot be described by one single pathway. In the future study, this pedigree can be extended by including the distal relatives of the family, which we believe can probably shed some light into the delineation of the pathological phenotype heterogeneity of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, one family member with ANFH (II-1) had a normal genotype compared with the other affected family members; further investigation into the identification of the possible mutated genes is required. In recent decades, >200 mutations have been identified in the COL2A1 gene, including single substitution, splice-site mutations and partial deletions ( 2 , 3 , 8 ). Type II collagen is a major component of the articular cartilage, which reduces articular friction and absorbs load pressure during movement.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors, including trauma, alcohol, steroids, coagulation disorders, sickle cell disease and fat embolism, have been reported to be implicated in the destruction of the femoral head ( 1 ). Avascular necrosis of the femoral head (ANFH), as a consequence of impaired blood supply, is a common type II collagenopathy that is associated with collagen type II α1 chain (COL2A1) mutations ( 2 , 3 ). The primary clinical manifestations of ANFH are limping gait, discrepancy in leg length and pain on exertion, which have a substantial effect on the quality of life of individuals ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%